2014
DOI: 10.1177/0095399714546326
|View full text |Cite
|
Sign up to set email alerts
|

Middle Managers’ Upward Roles in the Public Sector

Abstract: Whereas previous public administration studies have focused on middle managers' roles in implementation, this study contributes to the literature by emphasizing middle managers' other roles, specifically, upward roles that concern (a) championing alternatives and (b) synthesizing information. We examine whether middle managers are more involved in synthesizing information than championing alternatives and test multiple levers that increase these roles at the individual, organization, and interorganizational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 80 publications
(87 reference statements)
0
22
0
2
Order By: Relevance
“…Although we endeavoured to make our experimental design as robust as possible, there are some alternative explanations for our findings on bureaucrats' implementation intentions. In terms of bureaucratic discretion, we mainly conceptualise it by focusing on the level of discretion SLBs perceive in policy implementation, but variation in exercising discretionary power may be conditional on other factors, such as their personality or their relationship with superiors and middle managers (Prottas, 1979;Brehm and Hamilton, 1996;Riccucci et al, 2004;Tummers and Bekkers, 2014;Chen et al, 2017). If SLBs are able to build closer relationships with their elected politicians or they have a personality that leads them to be more open to a change, then it will positively affect bureaucrats' willingness to implement the politicians' policy change.…”
Section: Discussionmentioning
confidence: 99%
“…Although we endeavoured to make our experimental design as robust as possible, there are some alternative explanations for our findings on bureaucrats' implementation intentions. In terms of bureaucratic discretion, we mainly conceptualise it by focusing on the level of discretion SLBs perceive in policy implementation, but variation in exercising discretionary power may be conditional on other factors, such as their personality or their relationship with superiors and middle managers (Prottas, 1979;Brehm and Hamilton, 1996;Riccucci et al, 2004;Tummers and Bekkers, 2014;Chen et al, 2017). If SLBs are able to build closer relationships with their elected politicians or they have a personality that leads them to be more open to a change, then it will positively affect bureaucrats' willingness to implement the politicians' policy change.…”
Section: Discussionmentioning
confidence: 99%
“…Other such factors can be time availability and organizational boundaries as studied by Kuratko, Ireland, Covin, and Hornsby (2005). Similarly, a study by Chen, Berman, and Wang (2014) in public sector organizations found that job security, connections with stakeholders and autonomous motivation are some of the most important predictors of middle managers upward influencing roles. An acculturated view of issue selling is proposed by Ling, Floyd, and Baldridge (2005), where the authors argue that managers at lower tiers of an organization, socialized by different national cultures vary in their choice of issue selling and the degree to which their intent to sell issues is influenced by several contextual cues.…”
Section: Organization and Contextmentioning
confidence: 98%
“…Managerial control systems (Marginson, 2002) HR practices (Chen et al 2014;Hornsby et al 2002;Kuratko et al 2005;Mantere, 2005) Involvement in strategy process (Mantere, 2005;Vilà & Canales, 2008) TMT support (Hornsby et al 2002;Kuratko et al 2005;Mantere, 2008;Vuori & Huy, 2016;(Zimmermann, Raisch, & Birkinshaw, 2015) Formalization and decentralization…”
Section: Organizational Structure and Contextmentioning
confidence: 99%
“…Altman, 1979;Do¨ring et al, 2015). In particular, public managers can play a central role in promoting organizational responsiveness, innovation, and policy renewal (Chen et al, 2017;Vigoda, 2002).…”
Section: Introductionmentioning
confidence: 99%